PENGARUH SERVICE, CLEANLINESS, ORGANIZATION, DAN HEALTHINESS TERHADAP QUALITY PADA RESTORAN DI JAKARTA - DENNY SEPTA HARYANTI; NUNO SUTRISNO; LYVIA LYVIA (Media Bisnis, 2019)
The purpose of this study is to determine the effect of service, cleanliness, organization, and healthiness to quality of sushi tei restaurant in DKI Jakarta. The design of this study using descriptive research and causality research, the measurement of each variable using 5 points Likert scale. This study uses primary data and data collection through questionnaires. The research sample was obtained through a purposive sampling method and obtained as many as 145 respondents. The results of this study show that Organization has no effect to Quality, while Service, Cleanliness, and Healthiness have an influence to Quality.